2022
DOI: 10.3389/fnagi.2022.927295
|View full text |Cite|
|
Sign up to set email alerts
|

Use of electroencephalogram, gait, and their combined signals for classifying cognitive impairment and normal cognition

Abstract: BackgroundEarly identification of people at risk for cognitive decline is an important step in delaying the occurrence of cognitive impairment. This study investigated whether multimodal signals assessed using electroencephalogram (EEG) and gait kinematic parameters could be used to identify individuals at risk of cognitive impairment.MethodsThe survey was conducted at the Veterans Medical Research Institute in the Veterans Health Service Medical Center. A total of 220 individuals volunteered for this study an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…A higher percentile score indicates better cognition. Participants scoring ≤ 16th percentile were considered cognitively impaired [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…A higher percentile score indicates better cognition. Participants scoring ≤ 16th percentile were considered cognitively impaired [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For classifying healthy controls from those with AD, multimodal studies using MRI and PET data reported accuracy ranging from 74.3 [ 33 ] to 98% [ 52 ]. For discriminating MCI, AD and HC, the accuracy was generally lower with accuracies ranging from about 72–86% [ 52 , 55 ]. For classifying PD and HC with combined MRI and PET scan data, accuracies ranged from 88.57 [ 44 ] to 98.17% [ 31 ].…”
Section: Narrative Synthesis Of Relevant Findings From the Evidencementioning
confidence: 99%
“…There are 4 studies related to AD and 7 studies related to PD. The most common combination of data was movement data and speech (n = 5 studies) with one study focusing on AD [ 47 ] and 4 on PD [ 29 – 31 , 34 ], followed by movement data and EEG signals (n = 3 studies, with 1 study in AD and 2 in PD) [ 26 , 55 , 66 ].…”
Section: Narrative Synthesis Of Relevant Findings From the Evidencementioning
confidence: 99%
See 2 more Smart Citations